PENGARUH PRODUK DAN PROMOSI PENJUALAN TERHADAP VOLUME PENJUALAN PADA PT. DELAMIBRANDS KHARISMA BUSANA CABANG PALEMBANG - Syahyuni Syahyuni; Hisbullah Basri; Dimas Pratama Putra (JURNAL KOMPETITIF, 2021)
The Effect of Product and Sales Promotion on Sales Volume at PT Delamibrands Kharisma Busana Palembang Branch”. PT Delamibrands Kharisma Busana Palembang Branch In conducting this research, the authors used data collection techniques by means of interviews (interviews), questionnaires (questionnaires) and observations (observation). The questionnaire was distributed to 40 respondents who represent the population or who are the samples of this study. The data analysis techniques that the author uses are quantitative and qualitative analysis. For quantitative analysis, the author uses SPSS for Windows version 20.0. as a tool in calculating the questionnaire in order to get accurate results. From the results of the research that the author did, it was concluded that the Product variable ( ) as a variable that had a significant effect on Sales Volume at PT Delamibrands Kharisma Busana Palembang Branch with a tcount of 4,067 with a significant level of 0.000. While the other independent variable is Sales Promotion ( ) which also has a significant effect on Sales Volume with a tcount of 5.485 with a significant level of 0.000. For the overall independent variables which include Product ( ) and Sales Promotion ( ), then the Adjusted R square of 0.983 or 98.3% is obtained, which means that the correlation between X and Y is included in the strong category.